Framework and instruments of the European Union in the field of drugs (Office for Official Publications of the European Communities LuxembourgLU, 2002)
Looks at the legal framework. Examines the institutional framework focusing on the distribution of powers in the Union institutional set-up and the European Union's partners.
Keywords: DRUGS OF ABUSE